Capital Mobility in Developing Countries : M386Some Empirical Tests. (IMF Working Papers; Working Paper ;, 1990)
The degree of capital mobility in developing economies is seldom estimated, even though it is widely recognized to be an important element in determining the effects of stabilization policies. Instead, an economy is assumed to be open or closed mainly on grounds of analytical convenience. This paper develops a simple approach to modelling and measuring the degree of financial openness which is applicable to developing economies. Empirical estimation using data from a large number of developing countries suggests that the effective degree of capital mobility in such economies may be higher than is commonly assumed.